Tacit knowledge and spoken discourse - Zappavigna, Michele (Bloomsbury Academic, 2013)
Professional Linguistics is an emergent area of study within applied linguistics, using discourse analysis to assist people working in professional domains. This book examines tacit knowledge - that expertise that is considered to be lost when skilled practitioners leave an institution. Traditionally it has been argued that some aspects practical knowledge cannot be articulated. However, the premise of Polyani's theory of Tacit Knowing (""we know more than we can tell"") does not account for latent patterns that linguists can uncover in spoken language. Understanding these discourse patterns page